Efficient Entrapment of Oxirane Ring Containing Compounds in Thermally Stable Poly(urea-formaldehyde) Polymer Shell Wall - Ullah, H. (Pleiades Publishing, 2018)
This article aims to address the problems associated with the encapsulation of oxirane ring containing compounds in poly(urea-formaldehyde) (PUF) shell for application in self-healing composite systems. The main objectives were to produce non-agglomerated, stable microcapsules, and to control the pH drop during the encapsulation via oil-in-water emulsion polymerization. In the modified method; two stage additions of urea and formaldehyde monomers, core to shell ratio, weight percent and combination of two surfactants/emulsifiers were altered to produce the desired product. Analysis was done with optical microscope (OM), scanning electron microscopy (SEM), FTIR, particle size analyzer, and thermogravimetric analysis (TGA). The pH drop was confirmed by using a common epoxy resin, an epoxy functionalized polydimethylsiloxane (E-PDMS), and epoxidized palm oil (EPO) as cores. The modified oil-in-water emulsion polymerization of PUF was effective in preventing the pH drop during the encapsulation and a product stable for more than 3 months with less agglomeration was produced. The method produced microcapsules having diameters less than 100 Î¼m at lower agitation rates. The modified method is only applicable to epoxy resin and not for compounds like amine hardeners. The use of stable microcapsules in self-healing coatings can lead towards cost reduction implied for repair and maintenance purposes. Â© 2018, Pleiades Publishing, Ltd.